Effective exercise based training interventions targeting injury prevention in team-based sports: a systematic review - O'Malley, E.; Murphy, J.; Gissane, C.; McCarthy Persson, U.; Blake, C. (British Journal of Sports Medicine, 2014)
Background: Exercise-based training is proposed to aid injury prevention through enhanced neuromuscular-control and muscle strength. Objective: To assess the effects of exercise-based interventions on injury incidence in team sports. Design: Systematic review.Setting 5 electronic databases were searched (12/01/13) returning 275 unique articles. Participants: 23 randomised controlled trials (RCTs) involving 21,479 participants were included. Interventions Multifaceted exercise programmes were tested against controls (normal practice) in 12 studies, 7 studies used a balance board, 3 studies targeted hamstring strength and 1 study examined eccentric training of the Achilles and patellar tendons. Main outcome measurements: RCTs reporting overall or lower-limb injury incidence were included. Methodological quality of each trial was assessed using a tool developed by the Cochrane Bone, Joint and Muscle Trauma group (Goldman and Jones 2010). Meta-analysis was performed on homogenous studies using RevMan 5.1 software. Risk ratios (RR) and 95% confidence intervals (95% CI) were calculated using the Mantel-Haenszel method in a random effects model. Results: Pooled-analysis of multifaceted exercise programmes demonstrated a reduction in overall (RR=0.65, 95% CI=0.44-0.96, P=.03), knee (RR=0.79, 95% CI=0.63-0.99, P=.04), ACL (RR=0.51, 95% CI=0.28-0.93, P=.03) and ankle injury risk (RR=0.72, 95% CI=0.58-0.90, P=.003). Balance board interventions were shown to reduce hamstring (RR=0.22, 95% CI=0.05-1.02, P=.05) and ankle injury (RR=0.64, 95% CI=0.49-0.83, P=.001). Hamstring muscle training had no significant effect (RR=0.46, 95% CI=0.19-1.11, P=.09). Eccentric training of the Achilles and patellar tendons demonstrated an increased injury risk (RR=2.5, 95% CI=1.35- 4.61, P=.003). Conclusions: Exercise-based interventions can reduce injury risk in team sports. Strategies are required to translate this evidence into practice.